2015
DOI: 10.17795/jhealthscope-20667
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Affective Parameter on Cadmium Removal From an Aqueous Solution by Citrullus colocynthis Powdered Fruits by Response Surface

Abstract: Background: Cadmium is a toxic metal that occurs naturally in the environment and is considered as a pollutant emanating from industrial and agricultural sources. Biosorption is a very simple and cheap technique for removal of metal pollutants from aqueous samples. Objectives: In this study, removal of cadmium from aqueous solutions using C. colocynthis fruit powder was studied. Materials and Methods:The effect of three parameters such as pH, initial concentration of cadmium and adsorbent dosage were optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It can be observed that maximum % Pb(II) removal was obtained in the acidic range. Adsorbent dose and pH are the most important parameters adsorption studies [34] High adsorbent dose enhances complex formation between the metal ions and adsorbent. Fig.…”
Section: Figurementioning
confidence: 99%
“…It can be observed that maximum % Pb(II) removal was obtained in the acidic range. Adsorbent dose and pH are the most important parameters adsorption studies [34] High adsorbent dose enhances complex formation between the metal ions and adsorbent. Fig.…”
Section: Figurementioning
confidence: 99%